Heavy metals in plants grown on new fly ash deposits - Masu Smaranda; Rus Valeria; Jurj Luminita; Dragomir Nicolae; Uruioc Stela; International Symposium on Analytical and Environmental Problems (17.) (2011) (Szeged) Szeged 2011. szeptember 19. (SZAB Szeged, 2012)
The paper presents the results of studies with leguminous species grown on experimental parcels of new fly ash fertilized with biosolids (municipal sludge) and untreated indigenous volcanic tuff or pillared indigenous volcanic tuff. Fly ash comes from the dumps of ash from burning lignite in power plants. The resulting amount of biomass grown on new fly ash deposits is dependent on the treatment of topsoil (new fly ash). The experimental variants with new fly ash treated with biosolids and pillared indigenous volcanic tuff determined 50% germination and an increase of harvest by 2.5-2.7 times vs. others. In addition, the treatment of new fly ash with pillared indigenous volcanic tuff and biosolids caused a reduction in the bioaccumulation of heavy metals in the aerial part of plants by 35-45%, for Cu respectively Ni, 60 % for Cr, and 78% for Pb.
Keywords: Természettudományok; Kémiai tudományok; Biológiai tudományok; Mezőgazdaság-tudományok; Mezőgazdaság, erdészet, halászat